MENUMBUHKAN EKONOMI KREATIF DAN LITERASI KEUANGAN MELALUI WORKSHOP PEMBUATAN CELENGAN UNTUK SISWA SD - Suryani, Ermi; Amanda, Mutia; Rahmawati, Euis; Maesaroh, Siti Patimah; Agustina, Mila; Firdaus, M. Lazuardi; Agustian, Rizal; Bhasari, Galang Tri Septia (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2025)
Financial literacy in elementary school children is an important foundation in shaping responsible financial behavior. This community service program aims to improve financial literacy and introduce creative economic values through a workshop on making piggy banks from recycled materials for 6th grade students at SDN Cadasleueur Elementary School, Bogor Regency.The implementation method uses an experiential learning and learning by doing approach, divided into four stages: (1) introduction to the concept of financial literacy, 2) demonstration of piggy bank making,(3) independent practice, and(4) reflection and discussion.The results of the activity showed positive achievements with a 100% attendance rate (23 students),91% active participation (21 students),91% success in making functional piggy banks (21 students), and 100% understanding of the concept of saving.This workshop proved to be an effective,concrete, and enjoyable learning method for instilling the basics of financial literacy and the principle of utilizing used items in the context of the creative economy.